COVID-19 vaccination status in Germany: Factors and reasons for not being vaccinated (yet) - Sterl, Sebastian; Stelzmann, Daniela; Luettschwager, Nils; Gerhold, Lars (Frontiers in Public Health, 2023)
The Covid-19 pandemic has demonstrated that effective vaccines constitute a central element of successful pandemic control. Although everyone in Germany has had the opportunity to receive a Covid-19 vaccine, some people remain hesitant or refuse to get vaccinated. To address this phenomenon as well as examine the unvaccinated population more closely, the current study investigates (RQ1) factors explaining the Covid-19 vaccination status, (RQ2) trust in different types of Covid-19 vaccines as well as (RQ3) people’s specific reasons for not getting vaccinated against Covid-19. We base our findings on a representative survey that we conducted in Germany in December 2021 with 1,310 respondents. In response to the first research question, a logistic regression shows that trust in specific institutions (e.g., medical experts and authorities) is positively related to vaccination status, whereas trust in companies and Covid-19 related social and alternative media consumption decreases the likelihood of being vaccinated. Furthermore (RQ2), while vaccinated people trust mRNA-based vaccines (e.g., BioNTech), most unvaccinated people put greater trust in recently developed protein-based vaccines (e.g., Novavax), albeit on a low level. Finally, our study reveals (RQ3) that the most important reason why people choose not to get vaccinated is that they wish to make their own decisions about their body. Based on our results, we suggest that a successful vaccination campaign should address Covid-19 risk groups and lower income populations, increase trust in different public institutions and newly developed vaccines in advance, establish a multisectoral approach as well as debunk fake news and misinformation. Furthermore, since unvaccinated respondents state that the desire to make their own choices about their body is the main reason why they have not gotten vaccinated against Covid-19, an effective vaccination campaign should emphasize the need for general practitioners who have a closer relationship with their patients who, in turn, trust their doctors.